Seasonal population fluctuations of Bactrocera invadens (Diptera: Tephritidae) in relation to mango phenology in the Lake Victoria Crescent, Uganda. (17th October 2014) - Mayamba, Alex; Nankinga, Caroline Kukiriza; Isabirye, Brian; Akol, Anne Margaret
Abstract : Introduction . Timing of management practices requires an understanding of pest population dynamics in given cropping systems. Our study was designed to establish the population trends of B. invadens in mango orchards and to determine if population fluctuations were reflected in fruit infestation levels during changes in mango phenology.Materials and methods . Bactrocera invadens flies were trapped weekly from February 2011 to November 2012, using methyl eugenol and DDVP (dichlorvos) insecticidal strips. Trapping was done in three mango orchards in the Luweero district of Uganda's Lake Victoria Crescent. Mango fruit samples were incubated for the retrieval of puparia to calculate positivity (proportion of fruits infested) and fruit infestation indices (number of puparia per kg of fruit) for each stage of fruit maturity.Results . Mean trap catches of adult B. invadens varied significantly over the months (range : 11 flies per trap per day (FTD) to over 590 FTD; P £ 0.0001). During each year, infestations peaked during June-July and January-February. Trap catches were higher in the major fruiting season compared with the minor fruiting season and were the highest when mango was at the physiological maturity and ripe stages. Fruit infestation and positivity were highest for fruit at the physiological maturity and ripe stages and lowest at the fruit set stage.Discussion . Our findings show that B. invadens is present year-round and all stages of mango fruit development are susceptible to attack. Thus, control measures should be implemented throughout the year and preferably started at fruit set to lessen fruit fly population build-up and damage to fruits.